Neuronal and Glial Distribution of Tau Protein in the Adult Rat and Monkey - Kanaan, Nicholas M.; Grabinski, Tessa (Frontiers in Molecular Neuroscience, 2021)
Tau is a microtubule-associated protein for which the physiological functions remain a topic of vigorous investigation. Additionally, tau is a central player in the pathogenesis of several diseases such as Alzheimer’s disease and several frontotemporal dementias. A critical variable to understanding tau in physiological and disease contexts is its normal localization within cells of the adult CNS. Tau is often described as an axon-specific (or enriched) and neuron-specific protein with little to no expression in glial cells, all of which are untrue. Understanding normal tau distribution also impacts interpretation of experimental results and hypotheses regarding its role in disease. Thus, we set out to help clarify the normal localization of tau in the adult CNS of middle-aged rats and rhesus macaque using the hippocampus as a representative brain structure. The physiological concentration of tau in the rat hippocampus was 6.6 μM and in white matter was 3.6 μM as determined by quantitative sandwich ELISAs. We evaluated the cellular localization of tau using multiple tau-specific antibodies with epitopes to different regions, including Tau1, Tau5, Tau7, R1, and two novel primate-specific antibodies NT9 and NT15. In the rat and monkey, tau was localized within the somatodendritic and axonal compartments, as well as a subset of neuronal nuclei. Semi-quantitative fluorescence intensity measurements revealed that depending on the specific reagent used the somatodendritic tau is relatively equal to, higher than, or lower than axonal tau, highlighting differential labeling of tau with various antibodies despite its distribution throughout the neuron. Tau was strongly expressed in mature oligodendrocytes and displayed little to no expression in oligodendrocyte precursor cells, astrocytes or microglia. Collectively, the data indicate tau is 3 – 7 μM under physiological conditions, is not specifically enriched in axons, and is normally found in both neurons and mature oligodendrocytes in the adult CNS. The full landscape of tau distribution is not revealed by all antibodies suggesting availability of the epitopes is different within specific neuronal compartments. These findings set the stage for better understanding normal tau distributions and interpreting data regarding the presence of tau in different compartments or cell types within disease conditions.